The Mongolian gerbil as an advanced model to study cone system physiology - Günter, Alexander; Belhadj, Soumaya; Seeliger, Mathias W.; Mühlfriedel, Regine (Frontiers in Cellular Neuroscience, 2024)
In this work, we introduce a diurnal rodent, the Mongolian gerbil (Meriones unguiculatus) (MG) as an alternative to study retinal cone system physiology and pathophysiology in mice. The cone system is of particular importance, as it provides high-acuity and color vision and its impairment in retinal disorders is thus especially disabling. Despite their nocturnal lifestyle, mice are currently the most popular animals to study cone-related diseases due to the high availability of genetically modified models. However, the potential for successful translation of any cone-related results is limited due to the substantial differences in retinal organization between mice and humans. Alternatively, there are diurnal rodents such as the MG with a higher retinal proportion of cones and a macula-like specialized region for improved visual resolution, the visual streak. The focus of this work was the evaluation of the MG's cone system functionality using full-field electroretinography (ERG), together with a morphological assessment of its retinal/visual streak organization via angiography, optical coherence tomography (OCT), and photoreceptor immunohistochemistry. We found that rod system responses in MGs were comparable or slightly inferior to mice, while in contrast, cone system responses were much larger, more sensitive, and also faster than those in the murine counterparts, and in addition, it was possible to record sizeable ON and OFF ERG components. Morphologically, MG cone photoreceptor opsins were evenly distributed throughout the retina, while mice show a dorsoventral M-and S-opsin gradient. Additionally, each cone expressed a single opsin, in contrast to the typical co-expression of opsins in mice. Particular attention was given to the visual streak region, featuring a higher density of cones, elongated cone and rod outer segments (OSs), and an increased thickness of the inner and outer retinal layers in comparison to peripheral regions. In summary, our data render the MG a supreme model to investigate cone system physiology, pathophysiology, and to validate potential therapeutic strategies in that context.